Reaction pathways for in situ combustion (2015)
This study proposes reaction pathways to explain chemical routes that the fractions of a heavy crude oil follow during the thermal cracking and low temperature oxidation stages of in situ combustión (ISC). ISC is an enhanced oil recovery method that has as operating principle a combustion process inside a reservoir. Coke is produced during this process by thermal cracking and oxidation at low temperature and reacts to release energy in the form of heat that reduces the viscosity of the crude oil and facilitates its extraction. Current reaction schemes for ISC do not give details about the chemistry involved in this process. Based on that, this research studied the process from a chemical point of view in order to get a better understanding on the products formation and reactions. Surrogate compounds with physical and chemical properties representative of the dierent fractions of a crude oil were carefully selected. Given the complexity of the surrogate molecular structures, the reactive sites in the molecules were determined from the analysis of bond orders and reactivity indexes provided by electronic structure calculations. Quantum chemistry simulations of the posible reaction pathways of these surrogates indicated the most probable reactions that take place during ISC. Validation of the proposed reaction pathways was undertaken by assessing the agreement of intermediate species, products and reaction energies with experimental data available in the literature. The agreement was good and gave con dence that proposed pathways can improve the understanding of the chemistry associated with the ISC process and, therefore, enhance the probability of success of new ISC projects.